2009
DOI: 10.1038/nm.2065
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm-like extracellular viral assemblies mediate HTLV-1 cell-to-cell transmission at virological synapses

Abstract: Human T cell leukemia virus type 1 (HTLV-1) is a lymphotropic retrovirus whose cell-to-cell transmission requires cell contacts. HTLV-1-infected T lymphocytes form 'virological synapses', but the mechanism of HTLV-1 transmission remains poorly understood. We show here that HTLV-1-infected T lymphocytes transiently store viral particles as carbohydrate-rich extracellular assemblies that are held together and attached to the cell surface by virally-induced extracellular matrix components, including collagen and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
329
3
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 283 publications
(353 citation statements)
references
References 48 publications
12
329
3
9
Order By: Relevance
“…The size of the cytoplasmic enveloped virions was estimated as 153-155 nm and 171-183 nm on two different particles. No structures compatible with extracellular virions or viral biofilm (Pais-Correia et al, 2010) were detected by SEM at the surface of EGFP-positive 3867K cells (not shown), a result in accordance with the absence of an EGFP signal at the cell surface after 3D reconstruction (Fig. 1e).…”
Section: Marek's Disease Virus (Mdv) (Species Gallid Herpesvirus 2)supporting
confidence: 79%
“…The size of the cytoplasmic enveloped virions was estimated as 153-155 nm and 171-183 nm on two different particles. No structures compatible with extracellular virions or viral biofilm (Pais-Correia et al, 2010) were detected by SEM at the surface of EGFP-positive 3867K cells (not shown), a result in accordance with the absence of an EGFP signal at the cell surface after 3D reconstruction (Fig. 1e).…”
Section: Marek's Disease Virus (Mdv) (Species Gallid Herpesvirus 2)supporting
confidence: 79%
“…Engagement of these molecules is sufficient to trigger the reorientation of the MTOC in HTLV-1-infected T cells toward the cell-to-cell junction (26). Recent work also demonstrates that in both primary and cultured human lymphocytes, HTLV-1 viruses that bud from the cell surface can be entrapped within ECM and linker proteins reminiscent of bacterial biofilms (33). The findings of the current work are not in contradiction with prior data; rather, they demonstrate that HTLV-1 can also be transmitted by cellular conduits.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the requirement of cell-cell contact for viral transfer between lymphocytes. 41,42 Temperature dependence of the HTLV-1 passage and detection of viral particles within the Caco-2 cell cytoplasm by immunogold analysis at early steps (2 hours or less) strongly suggest transcytosis as an efficient mechanism of viral passage across a tight monolayer, which may occur in the first steps of HTLV-1 transmission. The existence of an HTLV-1 transcytosis mechanism across the enterocytes opens the question of the identification of HTLV-1 receptors that could be involved at the apical pole.…”
Section: Htlv-1 Passage Across Human Epithelial Barrier 577mentioning
confidence: 99%